In Vivo Biodistribution and Anti-Tumor Efficacy Evaluation of Doxorubicin and Paclitaxel-Loaded Pluronic Micelles Decorated with c(RGDyK) Peptide - Chen, Yanzuo; Zhang, Wei; Huang, Yukun; Gao, Feng; Fang, Xiaoling (PLOS ONE, 2016)
The treatment of squamous carcinoma, especially multidrug resistance (MDR) tumors, represents one of the most formidable challenges in oncology. In this study, integrin-mediated Pluronic-based micellar system (c(RGDyK)-FP-DP) was proposed as a drug delivery system to enhance the in vivo anti-tumor efficacy in MDR human squamous carcinoma (KBv)-bearing. Following the recognition by integrin proteins express on the cell surface, cellular uptake and in vitro anti-tumor efficacy of c(RGDyK)-FP-DP were better than conventional PF-DP in KBv cells. The tumor homing specificity and further in vivo anticancer efficacy of c(RGDyK)-FP-DP were performed using subcutaneous KBv tumor-bearing mice model, respectively. Compared with PF-DP, c(RGDyK)-FP-DP demonstrated more drug accumulation in tumor and relatively less drug accumulation in heart, and an extended median survival time in the KBv tumor-bearing mice model. Furthermore, preliminary in vivo subacute toxicity evaluation was also conducted by the measurement of histopathology, blood cell counts and clinical biochemistry parameters. Results showed that no obvious toxicity was observed to the hematological system or heart after a series of intravenous administration of c(RGDyK)-FP-DP. In conclusion, our results suggested that c(RGDyK) peptide conjugated Pluronic micelles could be a promising vehicle for enhancing the treatment of MDR human squamous carcinoma.